2020
DOI: 10.1021/acsinfecdis.0c00117
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the Amphotericin B Resistance Mechanisms in Candida haemulonii Species Complex

Abstract: The polyene amphotericin B (AMB) exerts a powerful and broad antifungal activity. AMB acts by (i) binding to ergosterol, leading to pore formation at the fungal plasma membrane with subsequent ion leakage, and (ii) inducing the intracellular accumulation of reactive oxygen species (ROS). Herein, we have deciphered the AMB resistance mechanisms in clinical isolates of Candida haemulonii complex (C. haemulonii, C. duobushaemulonii, C. haemulonii var. vulnera) in comparison to other clinically relevant non-albica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
(90 reference statements)
1
24
0
Order By: Relevance
“…Remarkable accumulation of ROS can result in oxidative stress and cellular components damage which are toxic to the organisms, even leading to autophagy, apoptosis or necrosis (Scherz-Shouval and Elazar, 2007;Nakagawa, 2008;Yu et al, 2016). AMB binds to ergosterol at plasma membrane causing loss of ions, induces ROS accumulation in different pathogenic fungal species (Mesa-Arango et al, 2014;Silva et al, 2020) and causes lipid peroxidation through a greatly increased ROS level and reactive nitrogen species (NOS) level (Ferreira et al, 2013). The ROS induction subsequently leading to apoptosis is an important mechanism of AMB in C. albicans (Francois et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkable accumulation of ROS can result in oxidative stress and cellular components damage which are toxic to the organisms, even leading to autophagy, apoptosis or necrosis (Scherz-Shouval and Elazar, 2007;Nakagawa, 2008;Yu et al, 2016). AMB binds to ergosterol at plasma membrane causing loss of ions, induces ROS accumulation in different pathogenic fungal species (Mesa-Arango et al, 2014;Silva et al, 2020) and causes lipid peroxidation through a greatly increased ROS level and reactive nitrogen species (NOS) level (Ferreira et al, 2013). The ROS induction subsequently leading to apoptosis is an important mechanism of AMB in C. albicans (Francois et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…VCZ MICs were not elevated, which differs from other studies ( 14 , 39 ). A recent Brazilian study has shown that resistance to oxidative stress along with changes in homeostasis, mitochondrial function, and ergosterol may be related to AmB resistance in the C. haemulonii complex ( 40 ). Cases of C. haemulonii complex are increasing according to recent reports, and more research is needed to understand antifungal susceptibility within the complex ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although AMB resistance has not been reported to be associated with the missing ergosterol in Aspergillus spp. ( Blum et al, 2008 , 2013 ), the absence of ergosterol in Candida spp., caused by mutations in genes of the ergosterol biosynthesis ( Geber et al, 1995 ; Sanglard et al, 2003 ; Martel et al, 2010a ; Vincent et al, 2013 ; Silva et al, 2020 ), leading to AMB resistance and abnormal membrane structure and function, which also drastically diminished tolerance to oxidative stress ( Vincent et al, 2013 ). These studies are consistent with the phenotypes observed in the AMB-resistant isolate of A. flavus .…”
Section: Discussionmentioning
confidence: 99%